2007
DOI: 10.1093/carcin/bgm183
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome proliferator-activated receptor-β/δ (PPARβ/δ) ligands do not potentiate growth of human cancer cell lines

Abstract: Ligands for peroxisome proliferator-activated receptor-beta/delta (PPARbeta/delta) increase skeletal muscle fatty acid catabolism, improve insulin sensitivity, increase serum high-density lipoprotein cholesterol, elicit anti-inflammatory activity and induce terminal differentiation. Contradictory findings are also reported suggesting that PPARbeta/delta ligands potentiate tumorigenesis by increasing cell proliferation, by inhibiting apoptosis through phosphorylation of Akt and by increasing cyclooxygenase-2 (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(75 citation statements)
references
References 53 publications
5
67
2
Order By: Relevance
“…4A,B). This result is consistent with recent studies showing no changes in the expression of PDPK1 and phosphorylation of AKT in response to GW0742 in human HaCaT keratinocytes and CRC cells 38, 39, 40. In addition, the levels of phosphorylated AKT were unchanged by knockdown of FABP5 (Fig.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…4A,B). This result is consistent with recent studies showing no changes in the expression of PDPK1 and phosphorylation of AKT in response to GW0742 in human HaCaT keratinocytes and CRC cells 38, 39, 40. In addition, the levels of phosphorylated AKT were unchanged by knockdown of FABP5 (Fig.…”
Section: Resultssupporting
confidence: 93%
“…Thus, these results strongly suggest that PPAR β/δ does not mediate the pro‐oncogenic activities of FABP5. Indeed, several lines of evidence have shown that PPAR β/δ signaling does not potentiate the growth of human cancer cell lines and attenuates colon carcinogenesis 39, 40, 41, 42. As shown in Fig.…”
Section: Resultsmentioning
confidence: 95%
“…After this treatment, mRNA was isolated and used for qPCR as described above. It is noteworthy that all of the cell lines have been shown to respond to ligand activation of PPAR␤/␦ and express PPAR␤/␦ mRNA (Hollingshead et al, 2007;Girroir et al, 2008a;He et al, 2008; and data not shown). However, relative expression of PPAR␤/␦ has been noted to be lower in these cancer cell lines compared with normal cells/tissue (data not shown).…”
Section: Phenyl)-5-thiazolyl)methyl)thio)phenoxy)-(gw501516) N-(2-bementioning
confidence: 91%
“…In a genetically modified animal model, intestinal tumorigenesis, but not colon carcinogenesis, was increased in response to GW501516 (Gupta et al, 2004). On the other hand, mice lacking PPAR␦ have an increased predisposition to intestinal tumors (Reed et al, 2004); other reports suggest that ligand activation of PPAR␦ is without effect (Hollingshead et al, 2007) or, in fact, inhibits growth of human cancer cell lines (Bility et al, 2008;Borland et al, 2008) and colon carcinogenesis in mice (Marin et al, 2006). PPAR␦ is a key regulator of skeletal muscle lipid oxidation, and, as outlined in section III, activation of PPAR␦ should have many potential beneficial effects in the context of metabolic disease.…”
Section: A What Will Be the Therapeutic Impact Of Peroxisome Prolifementioning
confidence: 94%